2018
DOI: 10.1093/nar/gkx1300
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of a bacterial t6A biosynthesis system

Abstract: The universal N(6)-threonylcarbamoyladenosine (t6A) modification at position 37 of ANN-decoding tRNAs is central to translational fidelity. In bacteria, t6A biosynthesis is catalyzed by the proteins TsaB, TsaC/TsaC2, TsaD and TsaE. Despite intense research, the molecular mechanisms underlying t6A biosynthesis are poorly understood. Here, we report biochemical and biophysical studies of the t6A biosynthesis system from Thermotoga maritima. Small angle X-ray scattering analysis reveals a symmetric 2:2 stoichiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(89 citation statements)
references
References 51 publications
9
69
0
Order By: Relevance
“…Sequence alignments with superposed secondary structure assignments of a few TsaB, TsaD and TsaE orthologues are represented in Supplementary Figure S1 . As illustrated in Figure 2a , Tm TsaB and Tm TsaD embrace Tm TsaE to form a compact ternary complex, in agreement with SAXS measurements on Ec - and Tm TsaBDE in solution ( 22 , 23 ). Tm TsaE is held in a grip between the helical insertion of the C-terminal domain of Tm TsaD on one side and Tm TsaB on the other.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Sequence alignments with superposed secondary structure assignments of a few TsaB, TsaD and TsaE orthologues are represented in Supplementary Figure S1 . As illustrated in Figure 2a , Tm TsaB and Tm TsaD embrace Tm TsaE to form a compact ternary complex, in agreement with SAXS measurements on Ec - and Tm TsaBDE in solution ( 22 , 23 ). Tm TsaE is held in a grip between the helical insertion of the C-terminal domain of Tm TsaD on one side and Tm TsaB on the other.…”
Section: Resultssupporting
confidence: 84%
“…In a very recent manuscript, Luthra et al . reported the characterization of the TsaBDE threonylcarbamoyl transfer complex of T. maritima ( Tm TsaBDE ) ( 23 ). Their SAXS analysis revealed that Tm TsaBDE forms a symmetric hexameric quaternary assembly in solution with 2:2:2 stoichiometry ( Tm TsaB 2 D 2 E 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This protein is indirectly responsible in the N6threonylcarbamoyladenosine (t(6)A) pathway. A study found that t6A involves in decoding accuracy of mRNA codons during protein synthesis [42]. Evidently, a defect in t(6)A pathway can lead to increased frame shift events, wrong start codon selections and occurrence of pleiotropic phenotypes [43].…”
Section: Potential Drug Design Candidatesmentioning
confidence: 99%